INOVASI PENGEMBANGAN APLIKASI PERPUSTAKAAN DIGITAL UNTUK OPTIMALISASI AKSES PENGETAHUAN DENGAN PENDEKATAN METODE WATERFALL - Musyaffa, Muhammad Ahnaffaiz; Utami, Wahyu Sri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The Digital Library application is a response to the rapid development of information technology, with the aim of increasing information accessibility, supporting literacy, and strengthening digital library services. This research uses literature study methods to review relevant theories, online surveys to understand user needs, in-depth interviews to explore user experiences, and web analytics to monitor user interactions with the application. The results show that CRUD (Create, Read, Update, Delete) operations play an important role in content management, allowing administrators to add, access, update and delete content efficiently. The use of full-text, metadata-based, and filter search features accelerates content access for users. In addition, these operations maintain the quality of information and ensure a better user experience. Thus, the app can overcome the limitations of traditional libraries and contribute to the improvement of literacy and knowledge collaboration globally.